Psychological and situational determinants of burnout in adolescent athletes - Markati, A.; Psychountaki, M.; Kingston, K.; Karteroliotis, K.; Apostolidis, N. (International Journal of Sport and Exercise Psychology, 2019)
Burnout in sport settings is commonly described as a multidimensional syndrome explained through a variety of antecedents. The present study aims to investigate the predictive relationship of psychological (motives, satisfaction, fatigue, anxiety, self-esteem) and situational (hours of training per week and perceived volume of training) determinants with athlete burnout symptoms (reduced sense of accomplishment, emotional/physical exhaustion, and sport devaluation). Participants were 142 Greek talented competitive athletes, aged 14-18 years, from various individual and team sports. Canonical correlation (CC) analysis indicated that the lack of satisfaction with performance, amotivation, and dysfunctional personality traits undermines athlete perceptions of accomplishment, while those less fatigued, less overloaded, and with a variety of motives protect themselves from feelings of emotional and physical exhaustion. Devaluation factor showed low reliability (.57) and thus was not included within CC analysis. Additionally, multivariate analysis of variance showed that "high burnout" athletes (n = 7) had elevated levels of amotivation, fatigue, and trait anxiety, but lower satisfaction with performance, less self-determined motivation, and lower self-esteem compared to "low burnout" athletes (n = 26). The present results highlight the need to take into consideration a combination of factors to understand burnout occurrence in adolescent athletes. Further, such athletes need to be supported in acquiring strategies to mitigate against threats to amotivation.